Pengaruh Inovasi dan Orientasi Pasar terhadap Keunggulan Bersaing Perusahaan - Ardyansyah, Ferry Dwi; Moko, Wahdiyat (Jurnal Kewirausahaan dan Inovasi, 2025)
The MSME industry is one of the most important sectors in the Indonesian economy, as it acts as the main driver of economic activity in various fields. Several researchers have revealed that competitive advantage can be influenced by innovation and market orientation. This study aims to determine how innovation and market orientation affect competitive advantage in the owners of culinary MSMEs in the field of snacks and cakes in Malang City. This study uses a sampling technique, namely non-probability sampling technique with purposive sampling method. The sample size used was 100 respondents of culinary MSMEs in the field of snacks and cakes in Malang City. The data analysis method used is multiple linear regression analysis using the SPSS 27 programme. The tools used to test this research instrument are validity test, reliability test and classical assumption test. Furthermore, hypothesis testing was carried out using the F test and t test. Based on the results of the analysis, it shows that (1) innovation has a significant effect on competitive advantage, (2) market orientation has a significant effect on competitive advantage.